Budaya Sibaliparriq dalam Perpektif Sosiologi Kebudayaan - Nasrullah; A. Nurkidam; Sulvinajayanti (IAIN Parepare, 2023)
This study aims to analyze how community solidarity is in the Sibaliparriq cultural identity in Tubo Tengah Village, and find out how Sibaliparriq culture forms both in family life and in community life. This study used a qualitative descriptive method, which seeks to provide a qualitative description of the cultural phenomena that occur in Tubo Tengah Village, with data collection techniques namely observation of research objects and interviews with informants in a structured manner, and documentation both in writing and using visual video. The data analysis technique used consists of data clarification stage, data reduction stage, data presentation stage and data verification or data conclusion. The results of research on Sibaliparriq Culture in the perspective of cultural sociology in Tubo Tengah Village show that the Sibaliparriq culture in Tubo Tengah Village has very close ties of social solidarity both in family and community life, for example, such as the establishment of intimacy in family life and among people, having concern for mutual assistance among society, people in their activities cooperate with each other regardless of differences in individual identity, live together in all activities in the environment. Meanwhile, the forms of solidarity in the Sibaliparriq Culture in Tubo Tengah Village show that the community forms the economic welfare of their respective families because they help each other in their family work, help each other and work together both within the family and within the community so as to produce an authentic cultural identity of Sibaliparriq